Analysis of the Relationship between Customer Satisfaction and Employee Job Satisfaction (Study at the Research Institute For Ornamental Fish Cultivation) - Endah Susiyanti; Mahendro Sumardjo; Faisal Marzuki (International Journal of Business, Technology and Organizational Behavior (IJBTOB), 2022)
The Purpose of this study was to analyze the relationship between customer satisfaction and employee job satisfaction with the variables of competence, innovation and work culture on employees at the Research Institute for Ornamental Fish Culture. The sample of respondents in this study were 84 employees and the sample selection used was through a questionnaire with a sample of all employees. Using quantitative methods with data analysis techniques using Partial Least Square (PLS). The results in this study indicate that employee competence has no effect on customer satisfaction, work culture has significant effect customer satisfaction, employee competence has an effect on job satisfaction, employee innovation affects job satisfaction, employee work culture has an effect job satisfaction, customer satisfaction effects job satisfaction, and competence, innovation and work culture simultaneously through Job satisfaction has no effect on customer satisfaction at the Ornamental Fish Cultivation Research Institute. Keywords : job satisfaction, competence,innovation, work culture, customer satisfaction